Overexpression and refolding of human Cyclin D3. A reliable method or not?. (December 2020) - Coelho, Fernanda; de Oliveira Pepino, Rebeka; Alencar, Diandra Pinheiro; Santos, Jessyka Lima; Canduri, Fernanda
Graphical abstract: Highlights: Overexpression of Cyclin D3 correlates with increased tumor growth in various types of cancer. Escherichia coli is one of the most widely used heterologous expression systems. Several refolding protocols have been used to solubilize proteins contained in inclusion bodies. Abstract: Cyclin D3 is a regulatory protein associated in a variety of human tumors. Despite several studies involving Cyclin D1 and D2, there are few articles that investigate the role of Cyclin D3. Therefore, this study aimed to produce and characterize Cyclin D3 using the Escherichia coli expression system and a protein refolding protocol. The anionic detergent SDS was used to solubilize the protein, then the solution were kept at 4 °C to precipitate SDS. After removing the precipitate by centrifugation, the supernatant was applied to the Ni-NTA column to purify His- tagged Cyclin D3. The recombinant protein shown to be refolded in a denaturation study by fluorescence spectroscopy at increasing concentrations of guanidine hydrochloride. The protein secondary structure, evaluated by circular dichroism, is composed of 39 % α helix and 15 % β-strands. In addition, the study aimed to validate the refolding protocol used to obtain Cyclin D3 from E. coli inclusion bodies.